THE MANAGEMENT STRATEGY OF SUGARCANE BUSINESS AS AN EFFORT TO INCREASE PG. MARITJAN KEDIRI'S REVENUE - Mahardiputra*, Qiqien Gunarko; Askafi, Eka; Mulyaningtiyas, Ratna Dewi (Jurnal Apresiasi Ekonomi, 2024)
The sugar industry's productivity is currently low because it is burdened with high overhead costs. Many sugar factory machines are old/antiquated, and sugar factory management is still inherited from the colonial era. The aim of this research is to find out sugar cane business management strategies as an effort to increase PG income Maritjan Kediri. A type of qualitative research that produces written or verbal descriptive data and observed behavior. The place where this research was carried out was in PG. Meritjan Kediri This research activity will be carried out for 2 (two) months, from February to March 2024. The research location chosen is the PG Meritjan sugar factory located within the PT. Sinergi Gula Nusantara with the consideration that PT Sinergi Gula Nusantara is a State-Owned Enterprise (BUMN) which has a sugar factory (PG) in East Java. This research uses primary data with sources consisting of farmer informants and Assistant Plant Managers. The analysis method uses SWOT analysis and Quantitative Strategy Planning Matrix (QSPM). SWOT analysis is a data analysis method used in this research using SWOT analysis. Reseacrh result are strategic factors in PG Management Strategy. Meritjan, namely; Internal strength factors include: (1) PG program planning. Meritjan is more participative; (2) The implementation of the sugar factory program is well coordinated with the role of the PG Sugarcane Farmers Cooperative. Meritjan; and (3) Well-coordinated evaluation. Keyword:Effort to Increase revenue, Management Strategy, Sugarcane Business